Development of a Discovery Learning Model Physics E-Book Containing Al-Qur'an Values to Improve Students' Problem-Solving Skills and Spiritual Attitudes - Bahtiar; Muhammad (Postgraduate, University of Mataram, 2024)
This research aims to develop a physics e-book discovery learning model containing Al-Qur’an values to improve students' problem-solving skills and spiritual attitudes. This research is included in the Research and Development type. This research refers to the 4D research and development model which consists of four development stages, there are define, design, develop, and disseminate. The resulting product development went through several test stages including validity and reliability testing, limited testing, and extensive testing. The validity test results show that the product is in the very valid category. In limited trials, it was seen that the product developed provided students with practical use in the classroom learning process. In extensive trials, it appears that the product being developed has a positive influence in improving students' spiritual attitudes and problem-solving skills. This is demonstrated based on the results of the effectiveness tests that have been carried out. Spiritual attitude is in the medium category, while problem-solving skills are in the high category. This research concludes that the development of a physics e-book discovery learning model containing Al-Qur’an values is able to improve students' problem-solving skills and spiritual attitudes.